2016
DOI: 10.1208/s12248-016-9979-x
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Lipids of the Lipoproteins in Trumenba, a Self-Adjuvanting Vaccine Against Meningococcal Meningitis B Disease

Abstract: ABSTRACT.Trumenba (bivalent rLP2086) is a vaccine licensed for the prevention of meningococcal meningitis disease caused by Neisseria meningitidis serogroup B (NmB) in individuals 10-25 years of age in the USA. The vaccine is composed of two factor H binding protein (fHbp) variants that were recombinantly expressed in Escherichia coli as native lipoproteins: rLP2086-A05 and rLP2086-B01. The vaccine was shown to induce potent bactericidal antibodies against a broad range of NmB isolates expressing fHbp that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 41 publications
3
55
0
Order By: Relevance
“…Diacylated and triacylated lipoproteins induce cell signalling by interacting with two different Toll‐like receptor 2 (TLR2) heterodimers on antigen presenting cells. Specifically, diacylated lipoproteins signal via TLR2/TLR6 heterodimers (Kang et al, ) and triacylated lipoproteins signal via TLR2/TLR1 heterodimers (Jin et al, ) and the latter was recently demonstrated for tripalmitoylated FHbp of Trumenba (Luo et al, ). This difference in signalling affects the ability of lipoproteins or lipopeptides to activate macrophages and subsequently to activate B cells (Metzger et al, , Mühlradt et al, , , Zeng et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Diacylated and triacylated lipoproteins induce cell signalling by interacting with two different Toll‐like receptor 2 (TLR2) heterodimers on antigen presenting cells. Specifically, diacylated lipoproteins signal via TLR2/TLR6 heterodimers (Kang et al, ) and triacylated lipoproteins signal via TLR2/TLR1 heterodimers (Jin et al, ) and the latter was recently demonstrated for tripalmitoylated FHbp of Trumenba (Luo et al, ). This difference in signalling affects the ability of lipoproteins or lipopeptides to activate macrophages and subsequently to activate B cells (Metzger et al, , Mühlradt et al, , , Zeng et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Despite differences in the efficiency of sorting of diacylated lipoproteins in Gram‐negative bacteria possessing the LolFD apparatus, the important question we now ask is whether these bacteria have the ability to naturally generate both di‐ and triacylated lipoproteins by regulation of Lnt. Whilst the lipid moieties of bacterial lipoproteins play an important structural role by anchoring the lipoprotein to the cell wall, during infection lipoproteins can dissociate from the bacterium freeing the exposed lipid moieties to exert their immuno‐modulatory activities (Luo et al, ). Diacylated and triacylated lipoproteins induce cell signalling by interacting with two different Toll‐like receptor 2 (TLR2) heterodimers on antigen presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“… 70 It was noted in preclinical in vivo studies that the lipidated forms of fHbps were more immunogenic compared to the non-lipidated forms, pointing to the self-adjuvanting activity of the TLR2-active moiety. 70 Our results suggest that diacyl or monoacyl TLR2 agonists that signal via TLR2/6 may be superior in eliciting adjuvant responses over triacyl species by promoting chemotactic responses to the site of injection. A careful comparison with MPLA (TLR4 agonist) would be useful in benchmarking the adjuvant properties of TLR2/6-active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Gas chromatography‐mass spectrometry (GC/MS) and liquid chromatography‐mass spectrometry (LC/MS) were used to analyze the composition of fatty acids released from rLP2086‐A05 and rLP2086‐B01 and for complete characterization of the primary structure of both recombinant lipoproteins. The LC‐MS analysis was carried out using an Acquity UHPLC/UV system interfaced to an ultrahigh‐resolution electrospray ionization quadrupole time‐of‐flight mass spectrometer (Bruker Daltonics maXis) …”
Section: Role Of Mass Spectrometry In the Vaccine Developmentmentioning
confidence: 99%